Beyond continuity institutional change in advanced political economies - Streeck, Wolfgang, 1946-; Thelen, Kathleen Ann (Oxford University Press, 2005)
"This book examines current theories of institutional change. The chapters highlight the limitations of these theories. Instead a model emerges of contemporary political economies developing in incremental but cumulatively transformative processes"--Provided by publisher.